Stage direction and the Novel from Early Twentieth Century to the Present. Two Perspectives (for an Introduction) - Marchetti, Marta; Peghinelli, Andrea (Status Quaestionis, 2022)
This introductory essay focuses on possible issues of the research on the relationship between drama and the novel in a century dominated by the director. Before introducing the articles, the editors suggest two different but complementary perspectives: the first is centred on issues concerning the authorship of the director, the second is an analysis of the recent phenomenon of the novelisation of contemporary dramaturgy.